Prothrombin Frankfurt: A Dysfunctional Prothrombin Characterized by Substitution of Glu-466 by Ala - Friezner Degen, Sandra J; McDowell, Susan A; Sparks, Leah M; Scharrer, Inge (Thrombosis and Haemostasis, 1995)
We have identified a patient with a dysfunctional prothrombin that we have designated Prothrombin Frankfurt. The proband was characterized by a prothrombin activity level of 13% and 20% compared to normal controls using two different assays with a normal prothrombin antigen level of 91% of normal controls. The genetic defect responsible for the abnormal prothrombin activity was determined by the polymerase chain reaction followed by single-strand conformation polymorphism (PCR-SSCP) analysis and by DNA sequence analysis of the human prothrombin gene. Substitution of a C for an A at nucleotide 10177 in the human prothrombin gene of the proband was identified, which results in the replacement of Glu-466 by Ala. The proband and one sister were homozygous for this mutation. Both parents, as well as one brother, were found to be heterozygous for this mutation. The same amino acid substitution was previously identified to be responsible for the dysfunctional protein Prothrombin Salakta and was hypothesized to result in altered substrate specificity. Four polymorphisms were also identified in the prothrombin gene from the proband when compared to the published sequence at nucleotides 554, 4048, 4272 and 10253.